2023
DOI: 10.1002/cbdv.202201190
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotics Induced Reproductive Toxicity by Stimulating Oxidative Stress: A Comparative in Vivo and in Silico Study

Abstract: The pathophysiological mechanism behind the link between antipsychotic drugs and sexual dysfunction is still unknown. The goal of this research is to compare the potential effects of antipsychotics on the male reproductive system. Fifty rats were randomly assigned into the five groups indicated: Control, Haloperidol, Risperidone, Quetiapine and Aripiprazole. Sperm parameters were significantly impaired in all antipsychoticstreated groups. Haloperidol and Risperidone significantly decreased the level of testost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
(174 reference statements)
0
1
0
Order By: Relevance
“…Antipsychotics have been used for the treatment of psychosis for decades, and their effects on the reproductive system have been investigated. 95 Recently, the results of an extensive cohort study on antipsychotic use have been published, and it has been reported that the use of antipsychotics in general during pregnancy is not directly related to malformation or neurodevelopmental disorder, except for the data of aripiprazole and olanzapine that require further research. 96 , 97 When a major congenital anomaly was evaluated, the risk was found to be 2.7% in babies of pregnant women who were not exposed to any antipsychotics, 4.3% in pregnant women using atypical antipsychotics, and 3.1% in babies using first-generation antipsychotics.…”
Section: Psychotropic Medicinesmentioning
confidence: 99%
“…Antipsychotics have been used for the treatment of psychosis for decades, and their effects on the reproductive system have been investigated. 95 Recently, the results of an extensive cohort study on antipsychotic use have been published, and it has been reported that the use of antipsychotics in general during pregnancy is not directly related to malformation or neurodevelopmental disorder, except for the data of aripiprazole and olanzapine that require further research. 96 , 97 When a major congenital anomaly was evaluated, the risk was found to be 2.7% in babies of pregnant women who were not exposed to any antipsychotics, 4.3% in pregnant women using atypical antipsychotics, and 3.1% in babies using first-generation antipsychotics.…”
Section: Psychotropic Medicinesmentioning
confidence: 99%